ABS composite material as well as preparation method and application thereof

By adding nylon resin and specific proportions of oleic amide and erucic amide to the ABS composite material, combined with ABS high glue powder, ABS composite material with excellent flexibility, scratch resistance and hydrophobic properties is prepared, which solves the problem of degradation of scratch resistance of existing ABS materials and achieves multiple performance improvements of the material.

CN119735901AActive Publication Date: 2025-04-01KINGFA SCI & TECH CO LTD

Patent Information

Application Number
CN202411652866.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-04-01
Estimated Expiration
2044-11-19

AI Technical Summary

Technical Problem

During the block splicing process, the existing ABS materials have significantly reduced scratch resistance due to rubber compression and shrinkage during the building block splicing process, and cannot meet the requirements of soft feel and scratch resistance at the same time.

Method used

By adding nylon resin and a specific proportion of oleic acid amide and erucic acid amide as surface modifiers to the ABS composite material, combined with ABS high glue powder, and melt blending and extruding using a twin screw extruder, ABS composite material with excellent flexibility, scratch resistance and hydrophobic properties was prepared.

Benefits of technology

ABS composite material has excellent softness, scratch resistance and stain resistance in building blocks, meeting the needs of simultaneously improving the soft feel and scratch resistance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005141407260000051
    Figure BDA0005141407260000051
  • Figure BDA0005141407260000061
    Figure BDA0005141407260000061
  • Figure BDA0005141407260000071
    Figure BDA0005141407260000071
Patent Text Reader

Abstract

The invention discloses an ABS (Acrylonitrile Butadiene Styrene) composite material as well as a preparation method and application thereof, and relates to the technical field of engineering plastics. The ABS composite material is prepared from the following raw materials in parts by weight: 44 to 67 parts of SAN (Styrene Acrylonitrile Butadiene Styrene) resin; 13 to 26 parts of high rubber powder; 9-32 parts of nylon resin; 0.8 to 7 parts of a surface modifier; the high rubber powder is ABS high rubber powder; the surface modifier comprises oleamide and erucyl amide, and the mass ratio of oleamide to erucyl amide is (1-5): (1-5). The ABS composite material provided by the invention has excellent softness, and also has excellent scratch resistance and stain resistance at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of plastics, and in particular to an ABS composite material and a preparation method and application thereof. Background Art

[0002] Common materials for building blocks include polypropylene, ABS, transparent ABS, etc. ABS has a high rubber content. During the building block assembly process, the rubber is squeezed and shrunk, giving the material a good soft feel. Therefore, ABS is a common material for toy building blocks. In order to get a better soft feel, more rubber is often added to ABS materials for building blocks, but this will significantly reduce the scratch resistance of the material. Therefore, it is necessary to develop a new ABS material that allows building blocks to have both an excellent soft feel and excellent scratch resistance. Summary of the invention

[0003] The purpose of the present invention is to overcome the shortcomings of the prior art and provide an ABS composite material and a preparation method and application thereof. The ABS composite material of the present invention has excellent softness, as well as excellent scratch resistance and stain resistance.

[0004] To achieve the above object, the technical solution adopted by the present invention is:

[0005] In a first aspect, the present invention provides an ABS composite material, wherein the raw materials of the ABS composite material include the following components in parts by weight:

[0006] SAN resin 44-67 parts; high-glue powder 13-26 parts; nylon resin 9-32 parts; surface modifier 0.8-7 parts; the high-glue powder is ABS high-glue powder; the surface modifier includes oleamide and erucamide, and the mass ratio of oleamide to erucamide is (1-5):(1-5).

[0007] SAN resin is a styrene-acrylonitrile copolymer.

[0008] The present invention, by adding nylon resin to the composite material, utilizes the self-lubricating property of nylon resin to not only improve the softness of the material, make the building blocks spliced ​​together easier to pull out, so that the material has a better soft feel, but also helps to reduce the content of high glue powder in ABS composite material, thereby improving the scratch resistance of the material. At the same time, by adding a surface modifier, it migrates to the surface of the material as an external lubricant, reduces the surface energy of the material, helps to improve the hydrophobicity of the material, thereby improving the stain resistance of the material. In addition, the present invention adopts ABS high glue powder, nylon resin and surface modifier compounding, so that the composite material has excellent scratch resistance and glossiness. At the same time, selecting a specific ratio of oleamide and erucamide for compounding is conducive to reducing the surface energy of the material, thereby further improving the hydrophobicity of the composite material.

[0009] Therefore, the present invention uses ABS high-rubber powder, nylon resin, and a specific ratio of oleic acid amide and erucic acid amide to cooperate with each other, which is not only beneficial to improving the scratch resistance and stain resistance of the composite material, but also makes the composite material have excellent softness.

[0010] Preferably, the nylon resin is PA6.

[0011] Preferably, the PA6 has a melt flow rate of 5-15 g / 10 min at 235° C. / 1.2 kg load according to ISO 1133-2011.

[0012] Preferably, the weight content of acrylonitrile in the SAN resin is 24-26%, the weight average molecular weight is 80,000-120,000, and the melt flow rate of the SAN resin at 220°C / 10kg load according to ISO 1133-2011 is 30-40g / 10min.

[0013] The test method for the acrylonitrile content in the SAN resin of the present invention is an infrared quantitative method: using the characteristic peak of the benzene ring at 1600cm in the infrared spectrum of the substance with known parameters -1 With the characteristic peak of acrylonitrile at 2237cm -1 The ratio K of the unknown substance is used to obtain a calibration curve of acrylonitrile content and ratio K, and then the acrylonitrile content is calculated based on the ratio 1600 / 2237 of the unknown substance.

[0014] Preferably, in the ABS composite material, the sum of the mass percentages of SAN resin and high-rubber powder is not less than 55%.

[0015] Preferably, the rubber content in the high-rubber powder is 40-60%, and the average particle size of the rubber is 300-400 nm.

[0016] The rubber particle size in the high-rubber powder of the present invention is measured by a dynamic light scattering method.

[0017] Preferably, the raw materials of the ABS composite material include the following components in parts by weight:

[0018] SAN resin 50-65 parts; high rubber powder 18-22 parts; nylon resin 15-25 parts; surface modifier 2-5 parts.

[0019] Preferably, the ABS composite material further comprises 0.3-1 parts of antioxidants and 0-1 parts of additives.

[0020] Preferably, the antioxidant is a hindered phenol antioxidant, specifically antioxidant 1010, antioxidant 1076, and antioxidant SONOX 1076.

[0021] Preferably, the additives include colorants and other lubricants, the other lubricants are amide lubricants or PETS lubricants, specifically lubricants EBS B50 and LOXIOL P 861 / 3.5; the colorants include organic dyes and inorganic dyes, specifically anthraquinone blue, anthraquinone violet, titanium dioxide, and carbon black.

[0022] In a second aspect, the present invention further provides a method for preparing an ABS composite material, comprising the following steps:

[0023] After the components are uniformly mixed, they are melt-blended and extruded on a twin-screw extruder, and then pelletized and dried underwater to obtain the ABS composite material.

[0024] Preferably, the processing temperature of the twin-screw extruder is 200-260° C., and the rotation speed is 350-600 rpm.

[0025] Preferably, the temperature of the first to second zones of the twin-screw extruder is 200-210°C, the temperature of the third to fifth zones is 220-230°C, the temperature of the fifth to tenth zones is 230-260°C, and the screw speed is 450-550rpm.

[0026] In a third aspect, the present invention further provides an application of an ABS composite material in building blocks.

[0027] The ABS composite material of the present invention has excellent softness, as well as excellent scratch resistance and stain resistance, and is suitable for toy building blocks.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] The present invention not only improves the softness of the material by adding nylon resin to the composite material, making the material have a better soft feel, but also helps to reduce the content of high rubber powder in the ABS composite material, thereby improving the scratch resistance of the material. At the same time, by adding a surface modifier, it migrates to the surface of the material as an external lubricant, reduces the surface energy of the material, improves the hydrophobicity of the material, and thus improves the anti-fouling performance of the material. DETAILED DESCRIPTION

[0030] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments, but the protection scope and implementation methods of the present invention are not limited thereto.

[0031] Unless otherwise specified, the materials and reagents used in the following examples are commercially available.

[0032] Examples 1-12

[0033] The embodiments of the ABS composite material and the preparation method thereof of the present invention, the components of the ABS composite material are shown in Table 1.

[0034] The preparation method of the ABS composite material comprises the following steps:

[0035] After uniformly mixing the components, melt blending and extrusion are performed on a twin-screw extruder, and then underwater pelletizing and drying are performed to obtain the ABS composite material;

[0036] The temperature of the twin-screw extruder is divided into ten zones, the temperature of zones one to two is 200-210°C, the temperature of zones three to five is 220-230°C, the temperature of zones five to ten is 230-260°C, and the screw speed is 450-550rpm.

[0037] Comparative Examples 1-9

[0038] The difference between each comparative example and the embodiment is only in the type and proportion of components, as shown in Table 2.

[0039] Among the components described in each embodiment and comparative example:

[0040] The SAN resin 1 is manufactured by Liaoning Jinfa, with a brand name of KFA-130, an acrylonitrile content of 24%, and a weight average molecular weight of 80,000;

[0041] The SAN resin 2 is from Tianjin Dagu, with a brand name of DG-AS106, an acrylonitrile content of 26%, and a weight average molecular weight of 120,000.

[0042] The high-rubber powder 1 is ABS high-rubber powder, the manufacturer is Kumho of South Korea, the brand is ABS POW HR181, the rubber content is 40%, and the average particle size is 300nm;

[0043] The high-rubber powder 2 is ABS high-rubber powder, the manufacturer is Shandong Yigong, the brand is ABS high-rubber powder EB-168, the rubber content is 60%, and the average particle size is 400nm.

[0044] The ASA rubber powder is manufactured by Kumho, South Korea, with a brand name of ASA POW XC640, a rubber content of 68%, and an average rubber particle size of 400 nm.

[0045] The nylon resin 1 is PA6, the manufacturer is Guangdong Xinhui Meida, the brand is PA M3400, and the melt flow rate at 235°C / 1.2kg load according to ISO 1133-2011 is 5g / 10min;

[0046] The nylon resin 2 is PA6, manufactured by Jiangsu Hongsheng New Materials Co., Ltd., with a brand name of PA6BE3280, and a melt flow rate of 10 g / 10 min at 235°C / 1.2 kg load according to ISO 1133-2011;

[0047] The nylon resin 3 is PA6, the manufacturer is Guangdong Xinhui Meida, the brand is PA6 M2400, and the melt flow rate at 235°C / 1.2kg load according to ISO 1133-2011 is 15g / 10min.

[0048] The surface modifier 1 includes oleamide and erucamide, and the mass ratio of the two is 1:5;

[0049] The surface modifier 2 includes oleamide and erucamide, and the mass ratio of the two is 1:1;

[0050] The surface modifier 3 includes oleamide and erucamide, and the mass ratio of the two is 5:1;

[0051] The surface modifier 4 includes oleamide and erucamide, and the mass ratio of the two is 1:6;

[0052] The surface modifier 5 includes oleamide and erucamide, and the mass ratio of the two is 6:1;

[0053] The surface modifier 6 includes oleamide and ethylene bisstearamide, and the mass ratio of the two is 1:1;

[0054] The surface modifier 7 includes ethylene bis stearamide and erucic acid amide, and the mass ratio of the two is 1:1;

[0055] The surface modifier 8 is oleamide;

[0056] The surface modifier 9 is erucamide;

[0057] The oleic acid amide is commercially available; the erucic acid amide is commercially available; and the ethylene bisstearic acid amide is commercially available.

[0058] The antioxidant is a hindered phenol antioxidant, which is commercially available.

[0059] The other lubricant is PETS lubricant, which is commercially available.

[0060] The colorant is anthraquinone blue.

[0061] Unless otherwise specified, the components and raw materials used in the embodiments and comparative examples of the present invention are all commercially available raw materials, and the components and raw materials used in each parallel experiment are all of the same kind.

[0062] Table 1

[0063]

[0064] Table 2

[0065]

[0066] In order to verify the performance of the ABS composite material of the present invention, the ABS composite materials prepared in each embodiment and comparative example were injection molded into test strips for testing the following properties.

[0067] Performance testing method:

[0068] 1. Insertion and extraction force: After injection molding 2×4 building blocks (length 32mm, width 16mm, height 10mm), the insertion and extraction force of the building blocks was tested on a fully automatic insertion and extraction force tester (model TG-9250); the insertion and extraction force range: 20-40N, the smaller the insertion and extraction force, the better the softness.

[0069] 2. Scratch resistance: After the color plate is injection molded, the pencil hardness is tested on a pencil hardness tester, referring to the standard GB / T6739-2006 for testing.

[0070] 3. Hydrophobicity: The rolling angle of the material to water is tested using a contact angle meter. The model of the contact angle meter is OSA200. The smaller the rolling angle, the better the hydrophobicity.

[0071] The performance parameters obtained from the above tests are shown in Tables 3 and 4.

[0072] Table 3

[0073]

[0074] Table 4

[0075]

[0076] According to Examples 1-12, the insertion and extraction forces of the ABS composite materials of the present invention are all lower than 30N, the pencil hardness is all above Grade B, the rolling angle is all lower than 30°, and while having excellent softness and scratch resistance, it also has excellent hydrophobic properties.

[0077] According to the comparison of Comparative Examples 7-9 with Example 2, it can be found that in Comparative Example 7, ASA rubber powder is used as high-grade rubber powder and compounded with nylon resin and surface modifier, and the scratch resistance of the composite material is not as good as that of Example 2. In Comparative Example 8, no nylon resin is added, and the softness of the composite material is affected; in Comparative Example 9, no surface modifier is added, and the hydrophobicity of the composite material is not as good as that of Example 2. In Example 2, ABS high-grade rubber powder is compounded with nylon resin and surface modifier, so that the composite material has excellent scratch resistance and softness, and also has excellent hydrophobicity.

[0078] According to the comparison between Comparative Examples 3-6 and Example 2, oleamide was added alone in Comparative Example 5, and erucamide was added alone in Comparative Example 6. The hydrophobicity of the composite materials in Comparative Examples 5-6 was not as good as that in Example 2, and the scratch resistance and softness were also not as good as those in Example 2, indicating that the composite materials of the present invention using oleamide or erucamide alone with nylon resin and surface modifier cannot have excellent softness while also having excellent scratch resistance and hydrophobicity. Comparative Examples 3-4 used oleamide or erucamide and ethylene bis stearamide, respectively, and the performance of the composite materials was not as good as that in Example 2, indicating that only by using oleamide and erucamide in combination can the composite materials have not only excellent softness, but also excellent scratch resistance and hydrophobicity.

[0079] By comparing Comparative Examples 1-2 with Example 2, it can be found that the mass ratio of oleamide and erucamide in Comparative Examples 1-2 is not within the range defined by the present invention, and the performance of the composite material is not as good as that of Example 2, which indicates that the present invention is beneficial to reducing the surface energy of the material by controlling the mass ratio of oleamide and erucamide, thereby further improving the hydrophobic properties of the composite material, and is also beneficial to improving the softness of the composite material.

[0080] According to Examples 4-6, as the content of nylon resin gradually increases, the insertion and extraction force gradually decreases, and the rolling angle gradually increases, indicating that the present invention can make the composite material have excellent hydrophobicity and softness by controlling the content of nylon resin.

[0081] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. An ABS composite material, characterized in that: The raw materials of the ABS composite material include the following components in parts by weight: SAN resin 44-67 parts; high-glue powder 13-26 parts; nylon resin 9-32 parts; surface modifier 0.8-7 parts; the high-glue powder is ABS high-glue powder; the surface modifier includes oleamide and erucamide, and the mass ratio of oleamide to erucamide is (1-5):(1-5).

2. The ABS composite material according to claim 1, characterized in that: The nylon resin is PA6, and the melt flow rate of PA6 at 235° C. / 1.2 kg load according to ISO 1133-2011 is 5-15 g / 10 min.

3. The ABS composite material according to claim 1, characterized in that: The rubber content in the high-rubber powder is 40-60%, and the average particle size of the rubber is 300-400nm.

4. The ABS composite material according to claim 1, characterized in that: The weight content of acrylonitrile in the SAN resin is 24-26%, and the weight average molecular weight is 80,000-120,000.

5. The ABS composite material according to claim 1, characterized in that: The SAN resin has a melt flow rate of 30-40 g / 10 min at 220° C. / 10 kg load according to ISO 1133-2011.

6. The ABS composite material according to claim 1, characterized in that: The raw materials of the ABS composite material include the following components in parts by weight: SAN resin 50-65 parts; high rubber powder 18-22 parts; nylon resin 15-25 parts; surface modifier 2-5 parts.

7. The ABS composite material according to claim 1, characterized in that: The ABS composite material also includes 0.3-1 parts of antioxidants and 0-1 parts of additives.

8. The ABS composite material according to claim 7, characterized in that: The antioxidant is a hindered phenol antioxidant, and the additives include colorants and other lubricants.

9. The method for preparing the ABS composite material according to any one of claims 1 to 8, characterized in that: The following steps are involved: After the components are uniformly mixed, they are melt-blended and extruded on a twin-screw extruder, and then pelletized and dried underwater to obtain the ABS composite material.

10. Use of the ABS composite material according to any one of claims 1 to 8 in building blocks.

Citation Information

Patent Citations

  • Polyethylene composition for bottle caps and preparation method thereof

    CN113896977A

  • Good-appearance enhanced SAN-PA66 composition as well as preparation method and application thereof

    CN118480262A

  • High-rigidity and high-toughness ABS (acrylonitrile butadiene styrene) composition as well as preparation method and application thereof

    CN118546473A

  • Thermoplastic resin composition and molded product thereof

    WO2022019411A1

Cited By

  • ABS / PA alloy material as well as preparation method and application thereof

    CN121136301A

  • Modified ABS composite material as well as preparation method and application thereof

    CN121271106A

  • Modified abs composite material, its preparation method and application

    CN121271106B